Street art, heritage and embodiment - Nomeikaite, Laima (2017)
In recent years, street art and graffiti have been framed as items of cultural heritage. However, until now, there has been no clear agreement on the definition or conceptualization of street art as heritage. This research presents limitations of the conventional approaches to heritage and argues that street art and graffiti does not represent a dichotomy between tangible and intangible heritage or people and object, but instead represents an inseparable relationship of the two. This study calls for greater engagement with more-than-representational approaches in studying the relationship between street art and heritage. More-than-representational approaches address street art’s crucial relationships with everyday life and change, as well as its relational, performative, embodied and affective components. Based on more-than-representational approaches, this research conceptualizes street art as a heritage experience in terms of embodiment, affect and everyday performativity. Furthermore, by situating the concept of embodiment within the case of Bergen, Norway, the paper provides an example of how the reasons and meanings behind the preservation of street artworks can be captured within a local context.